Pleiotropic biological effects of Lupinus spp. protein hydrolysates. (March 2023) - Cruz-Chamorro, Ivan; Santos-Sánchez, Guillermo; Álvarez-López, Ana Isabel; Pedroche, Justo; Lardone, Patricia Judith; Arnoldi, Anna; Lammi, Carmen; Carrillo-Vico, Antonio
Abstract: Background: Over the last two decades, the demand for meat-free food has increased for health, environmental, and animal welfare reasons. Thus, research on the value of vegetable compounds as beneficial agents for human health has gained much attention. In particular, great interest has been shown in protein hydrolysation since this food technology facilitates the release of encrypted peptides with biological activities. In this sense, during the last 10 years, the biological activities of Lupinus spp. protein hydrolysates (LPHs) have been extensively studied. Scope and approach: The aim of this review is to address all studies ( in silico, in vitro, and in vivo ) in which the biological activities (antioxidant, anti-inflammatory, etc.) of LPHs were described, both the whole hydrolysate and the derived peptides. Moreover, the physicochemical characteristics of LPH peptides are evaluated, and challenges and future perspectives for their fast application have been discussed. Key findings and conclusions: LPHs exert many important biological effects in both the in vitro and in vivo systems. The main activities of LPHs described are antioxidant, immunomodulatory, hypotensive, hypoglycemic, and hypolipidemic. These findings point to LPHs as a possible new nutraceutical for human health, capable of preventing or treating some chronic diseases such as diabetes, dyslipidemia, and atherosclerosis. Finally, the development of a new generation of nanonutraceuticals to improve the metabolic stability and bioactivity of LPHs has been discussed. Graphical abstract: Image 1 Highlights: Lupin protein hydrolysates (LPHs) act on the antioxidant and immune response. LPHs possess hypotensive and hypoglycemic effects. LPHs regulate cholesterol metabolism. LPHs reduce anxiety and osteoclastogenesis. LPHs-based nano-nutraceuticals synthesis.